PENDIDIKAN AKHLAK DALAM KITĀBUL ʽADAB DAN IMPLEMENTASINYA DI PONDOK PESANTREN ASY-SYIFA SUKOHARJO - Diki Fatkhan Ardiyansah; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2022)
Moral education is an educational effort that is very influential in shaping one's morality. A person who has good character is needed in order to avoid bad influences in the surrounding environment and cyberspace that can damage himself and others. Thus the more intelligent a person is through the educations taken, it will also be balanced with the strength of one's faith and piety so that the intelligence possessed is not used to oppress or harm others for personal gain. Asy-Syifa Sukoharjo Islamic Boarding School is one of the boarding schools that pays great attention to the moral education of its students. Pondok Asy-Syifa in educating the morals of its students specifically uses the basis of the Kitābul ʽAdab which is studied to its students using the manqul or ʽimlā’ method. The Kitābul ʽAdab itself is a book that contains the etiquette of a student and a collection of hadiths about adab. Learning the book of etiquette is not only taught its meaning, but also implemented to the students. This type of research is qualitative research through field research with psychological and phenomenological approaches. To obtain valid data, researchers used the method of observation, interviews and documentation. The objectives of this research are (1) to describe the contents of the study of the Kitābul ʽAdab at the Asy-Syifa Islamic Boarding School Sukoharjo, (2) to describe the implementation of the moral education program at the Asy-Syifa Islamic Boarding School Sukoharjo.